A meta‐synthesis of factors influencing nursing home staff decisions to transfer residents to hospital. (26th March 2015) - Laging, Bridget; Ford, Rosemary; Bauer, Michael; Nay, Rhonda
Abstract Aim To report a meta‐synthesis of qualitative research studies exploring the role of nursing home staff in decisions to transfer residents to hospital. Background Nurses and nurse assistants provide the majority of care to residents living in nursing homes and may be the only health workers present when a resident deteriorates. To inform future strategies, it is vital to understand the role of nursing home staff in decisions to transfer to hospital. Design and review methods A systematic review identified 17 studies to be included. The process of meta‐synthesis was undertaken using the Joanna Briggs Institute's guidelines. Data sources Qualitative research papers published between January 1989–October 2012 were identified in key databases including Cinahl, Embase, Medline and PsycInfo. Results Nursing home staff members play a key role in decision‐making at the time of a resident's deterioration. Multiple factors influence decisions to transfer to hospital including an unclear expectation of the nursing home role; limited staffing capacity; fear of working outside their scope of practice; poor access to multidisciplinary support and difficulties communicating with other decision‐makers. Conclusions There is a lack of consensus regarding the role of the nursing home when a resident's health deteriorates. Nursing home staff would benefit from a clear prescription of their expected minimum clinical skill set; a staffing capacity that allows for the increased requirements to manage residents on‐site, greater consistency in access to outside resources and further confidence and skills to optimize their role in resident advocacy.